Decoding the Pulse: Advancements in ECG Data Encryption - R. Mathusoothana S Kumar, Rajasree G (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The ever-advancing landscape of digital healthcare, it is crucial to securely transmit biomedical data, particularly the vital Electrocardiogram (ECG) signal, over the internet to hospital facilities. This study presents a novel encryption scheme for Electrocardiogram data by leveraging the Chaotic Baker map, Discrete Wavelet Transform and Dual Random Phase Encoding (DRPE). The methodology involves a three-step process designed to enhance security and effectively obscure original ECG information. The first step incorporates a randomized fusion of wavelet coefficients with a random signal, introducing variability. Subsequently, encryption scheme is implemented using 2-D Discrete Wavelet Transform (DWT) to mask the ECG signal and the speech signal, effectively concealing repetitive patterns. The third step employs DRPE, utilizing 2 Random Phase Masks (RPMs) to modify the spectrum of the transformed 2-D ECG signal. This multifaceted approach integrates random projection, salting, chaos-based encryption, and DRPE, providing a layered strategy for securing sensitive ECG data. Decryption involves the reverse application of these steps, ensuring the secure retrieval of the original ECG information. The proposed encryption methodology offers a robust solution for safeguarding ECG data across diverse applications.